Interplay Between Reading and Writing Under Different Teaching Models: A Study Based on Chinese Learning by China’s Ethnic Minorities - Zhang, Ying; Peng, Hengli; Bian, Yufang (Frontiers in Psychology, 2020)
Introduction: The relationship between reading and writing has been comprehensively explored from different perspectives. The following three theories and hypothesis could elucidate the relationship: reading→writing, writing→reading; and reading ↔writing. In China, the teaching models of school influence the Chinese language learning of students in ethnic minority areas. Although language teaching can take various forms, this study selects two teaching models (S1: the traditional teaching model; S2: the complete Chinese teaching model) that can broadly represent Chinese minority schools. Primarily, this study aims to investigate the impact of different teaching models on the interplay between Chinese reading and writing ability of China’s minority students. Second, this study aims to explore gender differences in the relationship between reading and writing in two different teaching models. Methods: As the cross-lagged model is suitable for a longitudinal study of the data collected from multiple time waves and explore the causal relationship between variables. We enrolled 3869 Chinese ethnic minority fourth- to sixth- grade students from 126 schools and collected data for three waves. This study mainly achieves the two aims mentioned above through the cross-lagged design. Results: Results reveal that: (1) the complete Chinese teaching model is more effective than the mixed teaching model in stimulating the interaction relationship between reading and writing; (2) in the mixed teaching model, boys did not exhibit a significant effect of reading on writing, but only the effect of writing on reading, whereas girls exhibited the interaction between reading and writing; in the complete teaching model, there are gender differences in the relationship between reading and writing, however, with the development of time, the interaction between boys and girls in reading and writing becomes more robust, demonstrating that similar development trend in boys’ and girls’ interaction between reading and writing. Conclusions: The implication of these results is that: (1) the interactive relationship between reading and writing is developed in both teaching models; (2) there are some gender differences in the relationship between reading and writing in each teaching model.